Caracterização genômica e estrutural das proteínas KKT ("Kinetoplastid KineTochore") de Trypanosoma cruzi - Cardoso, Thais De Oliveira [UNIFESP] (2019)
Cell division and the correct transmission of genetic material are essential for the survival of the living being. Many proteins ensure the accuracy and timing of these events by blocking changes that could result in damage to the cell. Proteins from DNA replication machinery are shared among eukaryotes, while the molecules involved in chromosomal segregation show sequence divergence. The identification in trypanosomes of centromeric and kinetochore proteins is hampered by the divergence between the primary sequence of these proteins from those of other eukaryotes. Recently, twenty Trypanosoma brucei kinetochore proteins were identified by mass spectrometry in the proteinassociated complexes whose transcripts increased during the cell cycle. The presence in Trypanosoma cruzi of KKT orthologous proteins (“Kinetoplastid KineTochore protein”) suggests their participation in the parasite's cell division. We analyzed the genomic organization in KKT9 orthologous and the presence of functional domains predicted by analysis of the primary amino acid sequence and structural motifs. Most KKT proteins are encoded by a pair of alleles, and also hemizigosis was detected in the clone CLB. The exception was the KKT11 protein which is encoded by five duplicate genes, distributed on four chromosomes, perhaps by retrotransposition. The low similarity among most KKT proteins is related to the origin and function of these proteins. KKT proteins have different origins and have been selected to act in the same biological process. The presence of conserved domains suggests that T. cruzi KKT proteins may be involved in important cell cycle steps and chromosomal segregation and have functions similar to those described in T. brucei. Experimental analyses will be needed to confirm these predictions. KKT9 protein was selected for more detailed structural and functional characterization in T. cruzi. The KKT9 is made up of a long and a short α-helix chains, connected together by a random-coil and turn handle region, forming a V-like shaped structure. Bioinformatics analyses found similarity between a region of KKT9 protein and the SMC proteins involved in the chromosomal condensation and sister chromatids cohesion during metaphase. In addition, the three-dimensional structure of KKT9 was aligned with the structures of two proteins important for the eukaryotic cell cycle (S. cerevisiae SMC and S. pombe septation protein-cdc11). The KKT9 gene was cloned into pGEX-1λT expression vector and the recombinant protein expressed in a heterologous system for antiboby production in mice. Polyclonal anti-KKT9 antibodies were used in western blotting analysis of expression of KKT9 protein throughout the cell cycle. We observed increased of the level of KKT9 protein in the S and G2 / M phases. Taken together data suggest the participation of KKT9 in T. cruzi chromosomal segregation.